The Role of Tutors in Growing Early Children's Interest in Reading at Vauz Studying Karangrejo Village, Wungu District, Madiun Regency - Jauhari, Mohamad Nasich (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
Having an interest in reading is more important than reading ability itself. Having the intention to read will encourage a person to have a desire to read which ultimately makes the child have the ability to read. An overview of the implementation of the role of a tutor as a creator, motivator, dynamist, supervisor, counselor and evaluator. This research was conducted using qualitative descriptives, using data through observation, interviews and documentation. The Miles and Hubberman model with 4 stages, namely collecting data, reducing, displaying data, and drawing conclusions or verifying data is used to analyze the collected data. The subjects in this research were Vauz Tutoring Tutors and Students. The research results show its role in growing interest in reading through several strategies, including inviting children to play, read and tell stories. Recommendations that can be given are for tutors to use more strategies to carry out their role in growing children's interest in reading.